Hong Kong's Cross-System University Partnerships. Issue 4 (2nd September 2016) - Postiglione, Gerard A.; Yunyun, Qin; Te, Alice Y.C.
Abstract: The authors examine the special case of Hong Kong higher education's institutional partnerships in the Chinese mainland. After noting the rise of cross-system university partnership in Asia, it provides a neoinstitutional perspective on the differences between the two China higher education systems. Finally, a case study of the experience of the longest-running Hong Kong campus partnership on the Chinese mainland is discussed and analyzed. Results show that while adaptations are required to sustain the partnership, the degree of autonomy has grown over time.